Beyond Commodities : The Growth Challenge of Latin America and the Caribbean - Araujo, Jorge Thompson (Washington, DC: World Bank, 2016)
Beyond Commodities shows that Latin America and the Caribbean’s growth performance over the last decade cannot be reduced to the commodity boom: growth-promoting reforms that strengthened financial development, increased trade openness and improved infrastructure development also played a significant role and can continue doing so. Based on the econometric analysis of panel data from the 1970-2010 period for 126 countries, the study shows that, while the commodity boom facilitated growth in most of the region, it did not determine it.